1991
DOI: 10.1164/ajrccm/143.1.150
|View full text |Cite
|
Sign up to set email alerts
|

A Positron Emission Tomographic Comparison of Pulmonary Vascular Permeability during the Adult Respiratory Distress Syndrome and Pneumonia

Abstract: We measured extravascular density (EVD) and the pulmonary transcapillary escape rate (PTCER) for 68Ga-transferrin using positron emission tomography in 14 normal volunteers and 29 patients with radiographic infiltrates, including six patients with congestive heart failure (CHF), eight patients with the adult respiratory distress syndrome (ARDS), and 15 patients with focal pneumonia. Contralateral, radiographically normal regions were also evaluated in the patients with focal pneumonia. Mean EVD was elevated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 9 publications
4
18
0
Order By: Relevance
“…As expected, high pulmonary vascular permeability is, however, non specific of ARDS, and has also been observed in patients with pneumonia [84]. Moreover, in a more recent study combining PET and mobile--scintigraphy data [86], there was considerable overlap regarding pulmonary vascular permeability between patients with hydrostatic and non-hydrostatic pulmonary edema, suggesting that structural damage of the alveolar-capillary membrane may also exist in hydrostatic pulmonary edema, as demonstrated by West et al as the stress capillary failure (West, 1992 #53683).…”
Section: Contribution Of Pet Studies To Ards Physiopathologysupporting
confidence: 79%
See 1 more Smart Citation
“…As expected, high pulmonary vascular permeability is, however, non specific of ARDS, and has also been observed in patients with pneumonia [84]. Moreover, in a more recent study combining PET and mobile--scintigraphy data [86], there was considerable overlap regarding pulmonary vascular permeability between patients with hydrostatic and non-hydrostatic pulmonary edema, suggesting that structural damage of the alveolar-capillary membrane may also exist in hydrostatic pulmonary edema, as demonstrated by West et al as the stress capillary failure (West, 1992 #53683).…”
Section: Contribution Of Pet Studies To Ards Physiopathologysupporting
confidence: 79%
“…Several studies have confirmed that pulmonary vascular permeability was high in ARDS patients, relative to normal human volunteers [16,83,84]. However, the regional correlation between vascular permeability and EVLW was relatively weak [83], and most patients exhibit diffuse increased vascular permeability, even in lung regions with normal density and EVLW [85], suggesting that lung density and EVLW are inadequate markers of ARDS.…”
Section: Contribution Of Pet Studies To Ards Physiopathologymentioning
confidence: 96%
“…In particular, this radiopharmaceutical could explore vascular permeability, which is typically increased in ARDS and not easily detectable by conventional techniques [93,94].…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Townsley et al 3 have suggested that alveolar-capillary barrier remodeling in a canine model of pacing-induced heart failure constitutes a beneficial adaptation to the pulmonary venous hyperperfusion that accompanies heart failure. Kaplan et al 18 documented a normal transcapillary escape rate of transferrin in patients with decompensated heart failure. Davies et al 19 have shown a reduced transferrin escape.…”
Section: Saline DL Co and Its Subdivisionsmentioning
confidence: 99%